Improving Early Childhood Language Development Through the Storytelling Method - Feiby Margaretha; Shofiyanti Nur Zuama; Nur Istiana Makarau; Andi Agusniatih (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2025)
The underdevelopment of children's language is associated with limited interaction during questioning, low engagement, and difficulties pronouncing sentences. This study aimed to improve children’s language development in Adhyaksa XXII Kindergarten by implementing a storytelling method. A classroom action research design following the Kemmis–McTaggart model was conducted across two cycles (four actions) to evaluate the effectiveness of a storytelling method in fostering an engaging, interactive, and imaginative learning environment for language acquisition. Data was collected through several methods, including observation, analysis of work results, checklists, and documentation. The results show that there was an increase in all indicators of children's language development after being given action. The improvement shows in the category of developing very well and developing as expected in cycle 1 by 45%, then there is an increase in cycle II to 80%, so that the increase that occurs is 35%, thus it can be concluded that the storytelling method can improve children's language skills in group B of Adhyaksa XXII Kindergarten in Palu. These findings indicate that storytelling proved an engaging and feasible way to enhance language acquisition.